PENGOBATAN HERPES ZOSTER (HZ) OPHTALIMICA DEXTRA DALAM JANGKA PENDEK SERTA PENCEGAHAN POSTHERPETIC NEURALGIA (PHN) - Sinaga, Dameria (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Herpes zoster is caused by opthalmica dextra varicella zoster virus. Infection which attacks skin and mucous. These infections are viral reactivation occuring after primary infection with the Symptoms are pain and paresthesia with cluster vesicel and erythematous base skin and edema. This disease. can be distinguished by herpes simplex.The objective of this paper is is to determine the treatment of herpes zoster in the short term as well as the prevention of postherpetic neuralgia. This paper is based on case studies of patients with Herpes Zoster the Dextra Ophtalmica hospitalized UKI. This research method is through direct observation (observasional case control study). It can be concluded that: (1) antiviral drugs should be given to patients of herpes zoster; especially older people with high risk of postherpetic neuralgia for reducing the pain and shorten the postherpetic neuralgia,Anti virus when given to reduce pain and short term postherpetic neuralgia,.(2) Corticosteroids may also reduce acute pain to reduce the risk of complications in herpes zoster ophtalmica.